2014
DOI: 10.1186/1472-6882-14-363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-sitosterol derived from Artemisia capillaris on the activated human hepatic stellate cells and dimethylnitrosamine-induced mouse liver fibrosis

Abstract: Backgroundβ-sitosterol is a cholesterol-like phytosterol, which widely distributed in the plant kingdom. Here, anti-fibrotic effect of the β-sitosterol was studied using the activated human hepatic stellate cell (HSC) model and dimethylnitrosamine (DMN)-induced mouse hepatic fibrosis model.MethodHSCs were activated by transforming growth factor-β (TGF-β) and the collagen-1 and α-smooth muscle actin (α-SMA) expressions were measured at the mRNA and protein level. We also studied the effect β-sitosterol using DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Liver fibrosis is a healing process that occurs in damaged liver tissues and can progress to liver cirrhosis or carcinoma [ 7 , 44 , 45 ]. The accumulation of fibrotic factors like collagen-1 and α -smooth muscle actin ( α -SMA) in the liver is attributable to hepatic stellate cells induced by the tumor growth factor- (TGF-) β or platelet-derived growth factor (PDGF) [ 46 ].…”
Section: Therapeutic Effects Of a Capillarismentioning
confidence: 99%
See 1 more Smart Citation
“…Liver fibrosis is a healing process that occurs in damaged liver tissues and can progress to liver cirrhosis or carcinoma [ 7 , 44 , 45 ]. The accumulation of fibrotic factors like collagen-1 and α -smooth muscle actin ( α -SMA) in the liver is attributable to hepatic stellate cells induced by the tumor growth factor- (TGF-) β or platelet-derived growth factor (PDGF) [ 46 ].…”
Section: Therapeutic Effects Of a Capillarismentioning
confidence: 99%
“…However, the statistical significance was not proven, and Artemisia iwayomogi rather than A. capillaris was more effective against the fibrotic changes [ 3 ]. The β -sitosterol derived from A. capillaris administered at 120 μ M and 40 mg/kg significantly regulated Col1A1 and α -SMA in LX2 cells and dimethylnitrosamine- (DMN-) induced fibrotic mice [ 7 ]. This effect was mediated by activating caspase-3, caspase-9, and Bcl-2-associated X protein (BAX) and inhibiting B-cell lymphoma 2 (Bcl-2), myeloid cell leukemia- (Mcl-) 1, phosphorylation of mitogen-activated protein kinase (MEK), and extracellular signal-regulated kinases (ERK) [ 7 ].…”
Section: Therapeutic Effects Of a Capillarismentioning
confidence: 99%
“…It is widely used in experimental animals, including mice, to create a low-mortality and reproducible model of liver cirrhosis (8,9). DMN significantly induces the deposition of collagen fibers and the formation of fibrous septa, as reported by previous studies (10,11), and as demonstrated by MT staining in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis frequently resulted from liver chronic damage can lead to development of liver cirrhosis and consequent failure of hepatic function. During the process of fibrogenesis, the proliferation and activation of HSCs are believed to play essential roles [ 24 , 25 ]. Therefore, suppression or reversal of HSC activation is considered as the main target of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%